THE IMPLEMENTATION OF RESTRUCTURING PROGRAM AND ACTIVITIES BASED ON THE MONEY FOLLOW PROGRAM IN REGIONS - Pranasari, Melati Ayuning; Fitri, Suci Emilia (Badan Pemeriksa Keuangan Republik Indonesia, 2020)
The current planning and budgeting paradigm has changed from money follows function into money follows program but this paradigm is considered to not provide clear and concrete benefits. Likewise, the implementation of the money follows program was still problematic, such as program restructuring and problematic activities. Based on these problems, the purpose of this study is to determine the implementation of restructuring programs and activities of local governments and the factors that support and hinder the implementation of restructuring programs and activities in local governments since the enactment of the money follows program. The method used in this study is a descriptive method with a qualitative approach. The results show that programs and activities planned by using the money follow program approach have been implemented in several locus study areas (West Sumatra Province, West Java Province, and Yogyakarta Province). However, the implementation still varies. There are still doubts for the regions in the implementation, especially because it is related to the legal basis. Likewise, there are several inhibiting factors such as human resources, policy substance, implementer behavior, and network interactions. For this reason, the study concludes that it is necessary to make adjustments to the central government policies related to regional development planning guidelines and budget allocation.